SITS – Simulator of Intelligent Transportation Systems - Figueiredo, Lino (2019)
This paper presents the most recent developments of the Simulator of Intelligent Transportation Systems (SITS). The SITS is based on a microscopic simulation approach to reproduce real traffic conditions in an urban or nonurban network. The program provides a detailed modelling of the traffic network, distinguishing between different types of vehicles and drivers and considering a wide range of network geometries. In order to analyze the quality of the microscopic traffic simulator SITS a benchmark test was performed.